Electrochemical Deoxygenation of Benzylic Alcohols and Electrosynthesis of Spirocycles - Edmonds, Alex (2024)
Electrosynthetic methods are of growing contemporary interest, due to the unique reactivity that they can facilitate, and their potential for improved sustainability compared to conventional methods. This thesis discusses the development of two different electrosynthetic reactions.